HDAC inhibition helps post-MI healing by modulating macrophage polarization. (June 2018) - Kimbrough, Denise; Wang, Sabina H.; Wright, Lillianne H.; Mani, Santhosh K.; Kasiganesan, Harinath; LaRue, Amanda C.; Cheng, Qi; Nadig, Satish N.; Atkinson, Carl; Menick, Donald R.
Abstract: Aims: Following an acute myocardial infarction (MI) the extracellular matrix (ECM) undergoes remodeling in order to prevent dilation of the infarct area and maintain cardiac output. Excessive and prolonged inflammation following an MI exacerbates adverse ventricular remodeling. Macrophages are an integral part of the inflammatory response that contribute to this remodeling. Treatment with histone deacetylase (HDAC) inhibitors preserves LV function and myocardial remodeling in the post-MI heart. This study tested whether inhibition of HDAC activity resulted in preserving post-MI LV function through the regulation of macrophage phenotype and early resolution of inflammation. Methods and results: HDAC inhibition does not affect the recruitment of CD45 + leukocytes, CD45 + /CD11b + inflammatory monocytes or CD45 + /CD11b + CD86 + inflammatory macrophages for the first 3 days following infarct. Further, HDAC inhibition does not change the high expression level of the inflammatory cytokines in the first days following MI. However, by day 7, there was a significant reduction in the levels of CD45 + /Cd11b + and CD45 + /CD11b + /CD86 + cells with HDAC inhibition. Remarkably, HDAC inhibition resulted in the dramatic increase in the recruitment of CD45 + /CD11b + /CD206 + alternatively activated macrophages as early as 1 day which remained significantly elevated until 5 days post-MI. qRT-PCR revealed that HDAC inhibitor treatment shifts the cytokine and chemokine environment towards an M2 phenotype with upregulation of M2 markers at 1 and 5 days post-MI. Importantly, HDAC inhibition correlates with significant preservation of both LV ejection fraction and end-diastolic volume and is associated with a significant increase in micro-vessel density in the border zone at 14 days post-MI. Conclusion: Inhibition of HDAC activity result in the early recruitment of reparative CD45 + /CD11b + /CD206 + macrophages in the post-MI heart and correlates with improved ventricular function and remodeling. This work identifies a very promising therapeutic opportunity to manage macrophage phenotype and enhance resolution of inflammation in the post-MI heart. Highlights: HDAC inhibition promotes the early and robust appearance of reparative M2 macrophages following MI. HDAC inhibition promotes the significant upregulation of M2 markers and non-inflammatory cytokines at 1 and 5 days post-MI. HDAC inhibition following MI does not affect the recruitment of M1 inflammatory macrophages out to day 3 post-MI HDAC inhibition promotes angiogenesis, limits LV dilation and preserves function in the post-MI ventricle